Global transcriptome analysis of Bacillus cereus ATCC 14579 in response to silver nitrate stress - Ganesh Babu Malli Mohan; Sridhar Jayavel; Gunasekaran Paramasamy (Journal of Nanobiotechnology, 2011)
Abstract Silver nanoparticles (AgNPs) were synthesized using Bacillus cereus strains. Earlier, we had synthesized monodispersive crystalline silver nanoparticles using B. cereus PGN1 and ATCC14579 strains. These strains have showed high level of resistance to silver nitrate (1 mM) but their global transcriptomic response has not been studied earlier. In this study, we investigated the cellular and metabolic response of B. cereus ATCC14579 treated with 1 mM silver nitrate for 30 & 60 min. Global expression profiling using genomic DNA microarray indicated that 10% (n = 524) of the total genes (n = 5234) represented on the microarray were up-regulated in the cells treated with silver nitrate. The majority of genes encoding for chaperones (GroEL), nutrient transporters, DNA replication, membrane proteins, etc. were up-regulated. A substantial number of the genes encoding chemotaxis and flagellar proteins were observed to be down-regulated. Motility assay of the silver nitrate treated cells revealed reduction in their chemotactic activity compared to the control cells. In addition, 14 distinct transcripts overexpressed from the 'empty' intergenic regions were also identified and proposed as stress-responsive non-coding small RNAs.